Corticosteroid use and mortality risk in patients with perforated colonic diverticular disease: a population-based cohort study. Issue 1 (1st April 2017) - Broersen, L H A; Horváth-Puhó, E; Pereira, A M; Erichsen, R; Dekkers, O M; Sørensen, H T
Abstract : Background: Corticosteroids are a potential risk factor for mortality in patients with perforated diverticular disease, due to blinding of disease severity, hampered wound healing or adrenal insufficiency. We examined mortality in corticosteroid users and non-users among patients with perforated diverticular disease. Methods: A cohort study based on medical databases including all patients ≥18 years in Denmark (source population 5 289 261 inhabitants) admitted to a hospital with incident perforated diverticular disease between 2005 and 2013. 7-day, 1-month, 3-month and 1-year mortality risks in corticosteroid users and non-users were calculated using the Kaplan–Meier method, and compared with Cox proportional hazard regression adjusted for age, sex and comorbidities. Results: The study included 4640 patients with perforated diverticular disease. Of these, 3743 (80.7%) had not used corticosteroids in the year before admission and 725 (15.6%) had been exposed to systemic corticosteroid treatment. The remaining 172 patients had been exposed to either inhaled or intestinal acting corticosteroid therapy. Mortality risk in non-users was 4.4% after 7 days and 15.6% after 1 year. This risk was doubled for corticosteroid users who filled their last prescription during the 90 days before admission, with mortality risks ranging from 14.2% after 7 days to 47.6% after 1 year. 1-year mortality risk was even higher for corticosteroid users with a first filled prescription ≤90 days before admission: 52.5%. Conclusions: Corticosteroid use was associated with clearly increased mortality risk after perforated diverticular disease. Thus, use of corticosteroids should be regarded as an important clinical prognostic factor for mortality in patients with this condition.